Elderly Patients with Mild Cognitive Impairment Exhibit Altered Gut Microbiota Profiles - Qiong Pan; Ya-Qian Li; Ke Guo; Min Xue; Yu Gan; Kejian Wang; Da-Bao Xu; Qiu-Yun Tu (Journal of Immunology Research)
Background. As a transitional state between normal aging and Alzheimer’s disease (AD), mild cognitive impairment (MCI) is characterized by a worse cognitive decline than that of natural aging. The association between AD and gut microbiota has been reported in a number of studies; however, microbial research regarding MCI remains limited. Methods. This study examined 48 participants, of whom 22 were MCI cases and 26 were normal control cases. Fecal samples were collected for 16S ribosomal RNA (rRNA) quantitative arrays and bioinformatics analysis. Results. A principal coordinates analysis (PCoA) and nonmetric multidimensional scaling (NMDS) both demonstrated that the microbial composition of participants with MCI deviated from that of healthy control participants. Multiple bacterial species were significantly increased (e.g., Staphylococcus intermedius) or decreased (e.g., Bacteroides salyersiae) in samples from the MCI group. Conclusion. The composition of gut microbiota differed between normal control and MCI cases. This is the first study to identify a signature series of species in the gut microbiota of individuals with MCI. The results provide a new direction for the future development of an early diagnosis and probiotic regimen.